GOALS AND OBJECTIVES OF SMALL BUSINESS AND ENTREPRENEURSHIP MANAGEMENT - Ismoilov Ravshanjon Bakhritdinovich; Muminov Sodiqjon Tukhtasinovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the goals and objectives of Small Business and Entrepreneurship Management.